1998
DOI: 10.1080/02724936.1998.11747933
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in children attending a major referral centre in Saudi Arabia

Abstract: Viral respiratory infections are common causes of illness in infants and children. Examination of clinical specimens submitted for diagnosis during a 3-year period (August 1993-July 1996) at King Faisal Specialist Hospital and Research Center (KFSH & RC) in Riyadh revealed a wide spectrum of diseases associated with the isolation of five respiratory viruses. Severity of disease ranged from mild upper respiratory illness to threatening lower respiratory illnesses including bronchiolitis and pneumonia. Of the 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
29
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 9 publications
11
29
0
1
Order By: Relevance
“…However, although group A viruses replicate to higher titers than group B viruses both in cell culture and in animals [18], studies evaluating relationship between RSV subtypes and disease severity have led to conflicting results [7,19,20]. Although we did not characterize the RSV subgroups in the two RSV seasons, the information that viruses within an individual group may be more virulent than others [7,19,20] and that, although temporal and geographic clustering may occur, different antigenic groups may co-circulate in a single epidemic period [12,[21][22][23][24], may at least partially explain our observations. Climate and environmental conditions may play a relevant role in RSV epidemics.…”
Section: Discussionmentioning
confidence: 75%
“…However, although group A viruses replicate to higher titers than group B viruses both in cell culture and in animals [18], studies evaluating relationship between RSV subtypes and disease severity have led to conflicting results [7,19,20]. Although we did not characterize the RSV subgroups in the two RSV seasons, the information that viruses within an individual group may be more virulent than others [7,19,20] and that, although temporal and geographic clustering may occur, different antigenic groups may co-circulate in a single epidemic period [12,[21][22][23][24], may at least partially explain our observations. Climate and environmental conditions may play a relevant role in RSV epidemics.…”
Section: Discussionmentioning
confidence: 75%
“…RSV is an important viral pathogen among hospitalized children in Saudi Arabia [51,52,53,54]. Most of these studies have identified respiratory viruses by conventional methods i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is consistent with previous reports from temperate regions where RSV causes epidemics every midwinter with peak prevalences in January to March. [3][4][5]22,28 In tropical countries, however, RSV causes outbreaks in the hot, rainy season from June to November. 1,6 The prevalence of RSV in the coldest months of the year in Zarqa could be related to the fact that rain and cold weather make people stay indoors, in crowded conditions, which facilitates transmission of RSV in children.…”
Section: Discussionmentioning
confidence: 99%